2017
DOI: 10.1016/j.arth.2017.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Do Medial Pivot Kinematics Correlate With Patient-Reported Outcomes After Total Knee Arthroplasty?

Abstract: A medial pivot pattern may not significantly govern clinical success after TKA based on intraoperative kinematics and modern outcome measures. Further research is warranted to determine if a particular kinematic pattern promotes optimal clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 29 publications
(27 reference statements)
2
35
0
Order By: Relevance
“…Thus, no conclusions can be drawn for other specific TKA designs. However, differently from previous studies where PS and CR designs were pooled together [19,21,23], the investigated cohort of the present study was highly homogenous. This might be considered a strength rather than an issue.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, no conclusions can be drawn for other specific TKA designs. However, differently from previous studies where PS and CR designs were pooled together [19,21,23], the investigated cohort of the present study was highly homogenous. This might be considered a strength rather than an issue.…”
Section: Discussionmentioning
confidence: 82%
“…Recently, Warth et al 23 published an article with different results. It was also aimed to determine whether intraoperative medial pivot kinematic patterns are associated with improved patient outcomes; however, at minimum 1-year FU, Knee Society objective, satisfaction, function, walking pain, stair pain, and the University of California Los Angeles (UCLA) activity level did not differ based on medial vs nonmedial pivot patterns.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the medially conforming total knee shows a medial pivot motion with tibial internal rotation. However, Warth et al [ 9 ] showed that a medial pivot pattern may not significantly govern clinical success after TKR based on intraoperative kinematics and modern outcome measures. They pointed out that further research is warranted to determine if a particular kinematic pattern promotes optimal clinical outcomes.…”
Section: Design Of Total Knee Replacementmentioning
confidence: 99%